2010
DOI: 10.1002/adfm.201001308
|View full text |Cite|
|
Sign up to set email alerts
|

Impedance Measurements as a Simple Tool to Control the Quality of Conjugated Polymers Designed for Photovoltaic Applications

Abstract: The problem of batch‐to‐batch variation of electronic properties and purity of conjugated polymers used as electron donor and photon harvesting materials in organic solar cells is addressed. A simple method is developed for rapid analysis of electronic quality of polymer‐based materials. It is shown that appearance of impurities capable of charge trapping changes electrophysical properties of conjugated polymers. In particular, a clear correlation between the effective relaxation time τeff and relative photovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…A metal can act as a charge recombination site to decrease J sc . [ 40 ] However, the present study also suggests that a large amount of metal impurities can in turn extend the charge carrier lifetime, which might assist the charge hopping or decrease the barrier at the electrodes, leading to the recovery of charge collection effi ciency to some extent under the short-circuit condition, although a total PCE would be still low.…”
Section: Impurity Effectmentioning
confidence: 93%
“…A metal can act as a charge recombination site to decrease J sc . [ 40 ] However, the present study also suggests that a large amount of metal impurities can in turn extend the charge carrier lifetime, which might assist the charge hopping or decrease the barrier at the electrodes, leading to the recovery of charge collection effi ciency to some extent under the short-circuit condition, although a total PCE would be still low.…”
Section: Impurity Effectmentioning
confidence: 93%
“…Several studies have previously demonstrated that P3HT molecular weight variations in the range of 10-20 kg mol À 1 do not significantly affect the morphology and device performance of the pristine polymer or P3HT/PCBM-based photovoltaics [22][23][24] . In addition, the Ni residues in the highly pure protonated and deuterated P3HT polymers synthesized for this study were measured by inductively coupled plasma mass spectroscopy to be less than 0.0014 wt.%, which is 50 times smaller than the threshold concentration of metal impurities for noticeable effects on device performance in previous studies [25][26][27] . Therefore, we exclude the impact of the molecular weight difference and metal residues on the measured optoelectronic properties between the deuterated and protonated P3HT polymers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…We utilised capacitance-voltage measurements in the dark to determine the degree to which a depletion region is present in the active layer. Capacitance-voltage measurements are an established technique used to determine the doping density of a semiconductor 6,19,29,38,[41][42][43] . The width of the space-charge region is probed by a variation of the DC voltage and is detected by measuring the capacitance of the device as a function of the DC voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Unintended or incomplete synthetic products have been shown to significantly reduce device efficiency and to be very difficult to detect 42,52 . Whether these could dope a device depends on the specific molecular properties.…”
Section: Discussionmentioning
confidence: 99%